Xenophobia towards asylum seekers: A survey of social theories. (March 2020) - Peterie, Michelle; Neil, David
In recent decades, there has been a global rise in fear and hostility towards asylum seekers. Xenophobia – or 'fear of the stranger' – has become a pressing issue in a range of disciplines. Several causal models have been proposed to explain this fear and the hostility it produces. However, disciplinary boundaries have limited productive dialogue between these approaches. This article draws connections between four of the main theories that have been advanced in the existing literature: (1) false belief accounts, (2) xenophobia as new racism, (3) sociobiological explanations and (4) xenophobia as an effect of capitalist globalisation. While this article cannot provide an exhaustive review of theories of xenophobia, it aims to present a useful comparative introduction to current research into the social aspects of xenophobia, particularly as these theories have been applied to asylum seekers. In bringing together divergent models, it also invites interdisciplinary engagement.